Furthering sustainability at Singapore Management University: A blueprint for blue skies - KONG, Lily (Institutional Knowledge at Singapore Management University, 2023)
On September 9, 2022, Singapore Management University (SMU) President Lily Kong launched the SMU Sustainability Blueprint at her fourth President’s State of the University Address to an audience of over 600 faculty, staff, students, and guests. While paying attention to sustainability was not new for SMU, this focus intensified from 2017, when plans were put in place to considerably reduce energy and water consumption, as well as waste, so that the whole of SMU could achieve a carbon neutral campus by 2030. In 2020, when the SMU 2025 Strategic Plan was announced, Sustainable Living was highlighted as one of the three strategic priorities of the university. In the following year, the SMU Sustainability Taskforce was formed, entrusted with crafting the Blueprint, which would chart actions in concerted ways across four key strategies supporting the Sustainability Living priority: Cultivate a Greener University, Develop Change Agents Through Sustainability Education, Drive Impactful Research, and Foster Resilient Communities. By September 2022, SMU had made considerable progress in its sustainability journey, but these efforts had also come with their share of challenges. Among the many difficulties encountered were tough decisions over ensuring that all the buildings were energy-efficient green buildings, fossil fuel divestment, interdisciplinary collaboration in the curriculum development for sustainability education, and the coalescence of disparate research efforts across the different schools. Attempts to build resilience within the SMU community during the COVID-19 pandemic – a period of disruptions, uncertainties, and stress – had not been easy too. Looking ahead, Kong contemplated: What else could she and all at SMU do to accelerate and deepen the university’s sustainability progress? What trade-offs would have to be made to achieve an ideal state of sustainable living?